1990
DOI: 10.1111/j.1745-4565.1990.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF OXYRASETM ENZYME ON LISTERIA MONOCYTOGENES AND OTHER FACULTATIVE ANAEROBES1

Abstract: The use of an oxygen-reducing membrane fraction to stimulate growth of some anaerobic bacteria has been reported. In this study, stimulated recovery of Escherichia coli 0157:H7. Salmonella typhimurium, Streptococcus faecalis, and heat-injured Listeria monocytogenes was achieved by using broth media supplemented with Oxyrase "' (membrane-bound enzyme system derived from E. coli). The Oxyrase" enzyme allowed rapid growth of these facultatively anaerobic organisms in a nonselective broth. The activity of Oxyrase"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…OxyraseTM enhances the growth of bacteria by removing oxygen and acting as a nutritional stimulator . It has the ability to stimulate the growth of the entire group of facultative anaerobic food pathogens, including Clostridium perfringens, Listeria monocytogenes, Salmonella spp., Campylobacter spp., E. coli 0 157: H7, and Yersinia enterocolitica during enrichment (Hoskins and Davidson 1988;Yu and Fung 1991;Fung 1992, 1994;and Phebus et al 1993). Excellent stimulation of growth for most strains of Arcobacter butzleri by OxyraseTM in a broth system was reported by Liu et al (1995).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…OxyraseTM enhances the growth of bacteria by removing oxygen and acting as a nutritional stimulator . It has the ability to stimulate the growth of the entire group of facultative anaerobic food pathogens, including Clostridium perfringens, Listeria monocytogenes, Salmonella spp., Campylobacter spp., E. coli 0 157: H7, and Yersinia enterocolitica during enrichment (Hoskins and Davidson 1988;Yu and Fung 1991;Fung 1992, 1994;and Phebus et al 1993). Excellent stimulation of growth for most strains of Arcobacter butzleri by OxyraseTM in a broth system was reported by Liu et al (1995).…”
Section: Introductionmentioning
confidence: 79%
“…OxyraseTM, a sterile membrane fraction of Escherichia coli, performs as an oxygen scavenger in the medium. The cytochrome-based electron-transport enzyme system present in the cytoplasmic membrane of E. coli results in the reduction of oxygen to water (Yu and Fung 1991). OxyraseTM enhances the growth of bacteria by removing oxygen and acting as a nutritional stimulator .…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 and 3). Other researchers have shown that OxyraseTM is most advantageous during the initial stages of enrichment (Phebus et al 1993;Yu and Fung 1991). During this period, GO provided the least growth stimulation.…”
Section: Influence Of Growth Of Pathogensmentioning
confidence: 87%
“…More recently, microbial membrane fractions such as OxyraseTM have been used to remove dissolved oxygen from media (Yu and Fung 1991). Several researchers (Yu and Fung 1991;Phebus et al 1993) have reported that OxyraseTM enhances the growth of Listeria monocytogenes, Escherichia coli 0157:H7, and other facultatively anaerobic microorganisms. Jacob (1970) pointed out that pH changes may cause variations in Eh and, thus, pH and redox measurements should be taken simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been done to improve recovery of sublethally injured L. monocytogenes cells by incorporating various chemicals into enrichment broths that either scavenge oxygen or degrade hydrogen peroxide (Busch and Donnelly 1992;Knabel et al 1990;Martin and Katz 1993;Yu and Fung 1991b). Hydrogen peroxide has been implicated as one of the major factors contributing to decreased survival and resuscitation of thermally stressed bacteria.…”
Section: Introductionmentioning
confidence: 99%